Chef Yasmina and the potato panic - Mannaert, Wauter (First Second, 2021)
Yasmina loves to cook, and her favorite thing to do is find a recipe from her cookbook and get some fresh vegetables from the community garden. But when a mysterious corporation bulldozes the garden and plants a strange new crop of potatoes that Yasmina's neighbors find irresistible, her world is turned upside down. Yasmina and her friends begin to investigate why the potatoes are turning people into crazy animals and come up with a plan to take down the company.